Operations, outreach and impact - Bioversity International (Bioversity International, 2015)
Bioversity International has a standing commitment to the long-term conservation of the global banana (Musa spp.) collection held in trust at the Bioversity International Musa Germplasm Transit Centre (ITC) in Leuven, Belgium under the auspices of the Food and Agriculture Organization of the UN (FAO). Those CGIAR Genebanks that fulfil the eligibility principles and criteria, and have reached performance targets, may enter into a long-term agreement with the Global Crop Diversity Trust. The ITC will reach these eligibility targets by the end of 2016.